2013
DOI: 10.1002/emmm.201201606
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 regulates differentiation of mesenchymal stem cells by deacetylating β‐catenin

Abstract: Mesenchymal stem cells (MSCs) are multi-potent cells that can differentiate into osteoblasts, adipocytes, chondrocytes and myocytes. This potential declines with aging. We investigated whether the sirtuin SIRT1 had a function in MSCs by creating MSC specific SIRT1 knock-out (MSCKO) mice. Aged MSCKO mice (2.2 years old) showed defects in tissues derived from MSCs; i.e. a reduction in subcutaneous fat, cortical bone thickness and trabecular volume. Young mice showed related but less pronounced effects. MSCs isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
171
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(187 citation statements)
references
References 68 publications
12
171
2
Order By: Relevance
“…Our results suggest that SIRT1 might be the primary deacetylase rendering SOX9 in a hypo‐acetylated state, similar to its action on various other regulators as β‐catenin, MyoD, and RelA (Fulco et al ., 2003; Yeung et al ., 2004; Simic et al ., 2013). A previous study, by Baltus et al .…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that SIRT1 might be the primary deacetylase rendering SOX9 in a hypo‐acetylated state, similar to its action on various other regulators as β‐catenin, MyoD, and RelA (Fulco et al ., 2003; Yeung et al ., 2004; Simic et al ., 2013). A previous study, by Baltus et al .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Chen et al which demonstrated overexpression of SIRT2 to interact with β-catenin in hepatocellular carcinoma (32), this is the first description of endogenous SIRT2 acting directly on β catenin–in untransformed cells of advanced chronologic age, demonstrating the potential for greater oxidative stress by IR and ROS mimics in aging tissues, specifically aging central nervous system, where SIRT2 is the predominant sirtuin isoform. Recently, Simic et al demonstrated that SIRT1 may be a therapeutic target to foster mesenchymal stem cell differentiation to preserve the integrity of mesenchymal stem cell-derived tissues in aging animals (33). In contrast, this manuscript demonstrates for the first time that SIRT2 may be potentiating the damage induced by IR in untransformed aging cells and that disruption of the SIRT2-β– catenin interaction may be an endogenous therapeutic target to preserve the integrity of aging cells against exogenous stressors such as IR.…”
Section: Discussionmentioning
confidence: 99%
“…In mesenchymal stem cells, SIRT1 is linked to differentiation towards bone and cartilage (Simic et al, 2013). In adult NSCs, loss of SIRT1 leads to increased self-renewal and proliferation with an increased production of oligodendrocytes (Rafalski et al, 2013), and similarly SIRT2 also acts to impede differentiation towards oligodendroglia (Li et al, 2007).…”
Section: Regulation Of Stem Cell Function By Histone Modificationsmentioning
confidence: 99%